Milton's political ideas and Paradise lost as a political allegory - Kiliç, Volkan (Cambridge Scholars Publishing, 2018)
Although Milton wrote several poems and sonnets in his earlier career, he became known as a revolutionary and passionate political activist, beginning his political career with the pamphlets that he wrote on the current politics of his time, defending antimonarchical rule and republicanism, giving particular attention to the religious and civil liberties of the people and the necessity of a free commonwealth. However, following the restoration of monarchy, he had to stop writing political pamphlets because, as a republican and defender of regicide, Milton was in danger, and the new regime made.